Self‐compatibility and autonomous selfing of plants in meadow communities. (20th October 2019) - Bartoš, M.; Janeček, Š.; Janečková, P.; Padyšáková, E.; Tropek, R.; Götzenberger, L.; Klomberg, Y.; Jersáková, J.
Abstract: One of the most fundamental, although controversial, questions related to the evolution of plant mating systems is the distribution of outcrossing rates. Self‐compatibility, and especially autonomous self‐pollination, can become particularly beneficial in anthropogenically degraded habitats with impoverished pollinator assemblages and increased pollen limitation. In a hand‐pollination experiment with 46 meadow plants from the Železné hory Mts., Czech Republic, we evaluated the species' ability to adopt different mating systems. For a subset of the species, we also tested seed germination for inbreeding depression. Subsequently, we analysed relationships between the species' mating systems and 12 floral and life‐history traits. We found a relatively discrete distribution of the studied species into four groups. Fully and partially self‐incompatible species formed the largest group, followed by self‐compatible non‐selfers and mixed mating species. The germination experiment showed an absence of inbreeding depression in 19 out of 22 examined species. Nectar sugar per flower, nectar sugar per shoot and dichogamy were significant associated with the mating system. Spontaneous selfing ability and self‐incompatibility in species of the meadow communities had a discrete distribution, conforming to the general distribution of mating and breeding systems in angiosperms. The low frequency of spontaneous selfers and the lack of inbreeding depression at germination suggest the existence of a selection against selfing at the later ontogenetic stages. Some floral traits, such as the level of dichogamy and amount of nectar reward, may strongly impact the balance between selfing and outcrossing rates in the self‐compatible species and thus shape the evolution of mating systems. Abstract : Spontaneous selfing ability and self‐incompatibility of plants in meadow communities had a discrete distribution, and nectar sugar per flower and per shoot, as well as dichogamy showed significant associations with the mating system.